گاما رو نصب کن!

{{ number }}
اعلان ها
اعلان جدیدی وجود ندارد!
کاربر جدید

جستجو

پربازدیدها: #{{ tag.title }}

میتونی لایو بذاری!

برای دو تابع $f=\{(-1,a),(2,1),(b,2)\}$ و $g=\{(-2,-1),(c,3),(-3,\frac{1}{3})\}$ اگر داشته باشیم: $(fog)(-2)+(fog)(1)=5$، حاصل $a+b+c$ کدام است؟

1 ) 

$9$

2 ) 

$8$

3 ) 

$7$

4 ) 

$6$

پاسخ تشریحی :
نمایش پاسخ

$(fog)(-2)=f(g(-2))=f(-1)=a$

تعریف شده است $(fog)(1)\Rightarrow 1\in {{D}_{g}}\Rightarrow c=1,g(1)\in {{D}_{f}}$

$\Rightarrow 3\in {{D}_{f}}\Rightarrow b=3$

$(fog)(-2)+(fog)(1)=5\Rightarrow a+2=5\Rightarrow a=3$

$a+b+c=3+3+1=7$

تحلیل ویدئویی تست

جواد راستگویان